Selective Removal of Toxic Metals like Copper and Arsenic from Drinking Water Using Phenol-Formaldehyde Type Chelating Resins - Debasis Mohanty; Shashadhar Samal (E-Journal of Chemistry)
The concentration of different toxic metals has increased beyond environmentally and ecologically permissible levels due to the increase in industrial activity. More than 100 million people of Bangladesh and West Bengal in India are affected by drinking ground water contaminated with arsenic and some parts of India is also affected by poisoning effect of copper, cadmium and fluoride. Different methods have been evolved to reduce the arsenic concentration in drinking water to a maximum permissible level of 10 μg/L where as various methods are also available to separate copper from drinking water. Of the proven methods available today, removal of arsenic by polymeric ion exchangers has been most effective. While chelating ion exchange resins having specific chelating groups attached to a polymer have found extensive use in sorption and pre concentration of Cu2+ ions. Both the methods are coupled here to separate and preconcentrate toxic metal cation Cu2+ and metal anion arsenate(AsO4–) at the same time. We have prepared a series of low-cost polymeric resins, which are very efficient in removing copper ion from drinking water and after coordinating with copper ion they act as polymeric ligand exchanger, which are efficiently removing arsenate from drinking water. For this purpose Schiff bases were prepared by condensing o-phenylenediamine with o-, m-, and p-hydroxybenzaldehydes. Condensing these phenolic Schiff bases with formaldehyde afforded the chelating resins in high yields. These resins are loaded with Cu2+, Ni2+ 2+, and Fe3+ ions. The resins and the polychelates are highly insoluble in water. In powdered form the metal ion-loaded resins are found to very efficiently remove arsenate ion from water at neutral pH. Resins loaded with optimum amount of Cu2+ ion is more effective in removing arsenate ions compared to those with Fe3+ ion, apparently because Cu2+ is a stronger Lewis acid than Fe3+. Various parameters influencing the removal of the arsenate ion from drinking water to a concentration level below 20 μg/L are studied.